Comparison of the level of training of professionals in the area of healing in diabetic foot: report of two cases (Jóvenes en la Ciencia, 2024)
Several authors have demonstrated the impact of the training of nursing staff in the treatment of diabetic foot, such as the studies carried out by Hermes Sandro, Huayna Canteño and Borja Ramos, which show how this knowledge affects nursing professionals when performing cures on patients.OBJECTIVE: To compare nursing knowledge and practice in the area of cures in the treatment of diabetic foot in two CAISES in Irapuato, Guanajuato. This is an observational, descriptive and cross-sectional study. A survey was conducted with 2 nurses in charge of the healing area of different CAISES, during the period January-July 2024. Nursing graduates obtained 81.81% of correct answers, this showed us that they are moderately trained within the field. During the observation of the technique of both graduates, 16 nursing care equivalent to 100% were evaluated, where the CAISES of Purisima complied in 81.25%, equivalent to moderate training and Colón in 75%, which refers to it as slightly trained. These results suggest that the nursing staff in the healing areas is moderately trained for the pertinent care related to diabetic foot care.